Spin-off Decision Making in Islamic Windows of Financing Companies - Oktaviani, Intan Herlina; Prasetyo, Muhammad Budi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
Decision-makers must consider many factors in carrying spin-off. The previous literature discussed more results on academics, non-financial companies, or Islamic banking. This paper proposes essential criteria to use in the analysis of financing company spin-off decisions. This article uses the AHP method by distributing questionnaires to the Directors of financing companies entitled to make spin-off decisions to determine the priority of the criteria and sub-criteria in question. The results show that financial condition is an essential criterion in making spin-off decisions. As for the Islamic financing business concept and strategy, the rate of return and growth are the top ranks for the sub-criteria chosen by the spin-off decision-maker.